DIGITAL TECHNOLOGIES IN MATHEMATICS EDUCATION - Adeilton de Oliveira Andrade, Emanuel; Pessoa da Silva, Isaías; Oneide Meneses Pina, Maria (Journal of Interdisciplinary Debates, 2023)
The article reviews conceptions to recognize pedagogical practices, elucidating how digital technological elements contribute to education. The study addresses the importance of understanding the benefits and challenges of integrating digital technologies into education, and discusses how these resources can promote innovation and the development of new pedagogical practices? In addition to suggesting, that computer, math software, websites and online tutorials, with this, students can access information about mathematics quickly, making it easier for them to learn and apply math concepts. In this perspective, it should be considered that digital média can be useful when used in a responsible and educational way to build knowledge, because they offer teachers and students a wide variety of resources to use in the classroom. This text aimed to bring a reflection on the technologies used in mathematics class. This discipline requires a lot of dedication and study. In a way, technological resources can certainly be useful for improving the quality of teaching and learning.